Technical comment on "sex ratios when helpers stay at the nest". (18th January 2023) - Wild, Geoff
Abstract: I contributed a paper to volume 60 of the journal. The paper reported on my study of sex-ratio evolution when one sex (females) is helpful but the other sex (males) suffers less from kin competition. I had based my study on a kin-selection model, and so I was dismayed to discover an error in the relatedness calculations therein. Specifically, relatedness coefficients that should have been calculated using a sampling-without-replacement scheme were instead calculated using sampling with replacement. Here, I correct my error and show how it impacts my original findings. I argue that my main conclusions are unchanged. Furthermore, only two new findings contrast with those I presented earlier. First, changing those model details unrelated to the marginal fitness benefits of help does not, in turn, impact substantially the conflict that occurs between mates over the brood sex ratio (I had previously reported some noteworthy impact was possible). Second, help can reduce sex-ratio conflict between mates more effectively when breeders occur in smaller groups (previously, I had said this occurred in larger groups).